Sosialisasi Kewirausahaan dan Regulasi Hukum dalam Era Digital di Kecamatan Tembilahan Hulu, Desa Pulau Palas - Feni Puspitasari; Darmiwati (Universitas Islam Indragiri, 2025)
This program aims to enhance the understanding of digital entrepreneurship among the residents of Pulau Palas Village, Tembilahan Hulu District, through a simulation-based and direct implementation approach. The activities began with a simulation covering fundamental digital entrepreneurship concepts, marketing strategies, and the utilization of digital platforms such as marketplaces and social media. After the simulation, participants applied the acquired knowledge by developing products or services, creating marketplace accounts, and executing digital marketing strategies. Additionally, they were guided in basic financial management and periodic business evaluations. This program resulted in increased community awareness of digital business, empowered the local economy, and expanded market access through technology. With continuous evaluation and mentoring, participants are expected to develop sustainable digital businesses and contribute to the village’s economic growth.